Best Answer

5ex+2?

d/dx(u+v)=du/dx+dv/dx

d/dx(5ex+2)=d/dx(5ex)+d/dx(2)

-The derivative of 5ex is:

d/dx(cu)=c*du/dx where c is a constant.

d/dx(5ex)=5*d/dx(ex)

-The derivative of 2 is 0 because it is a constant.

d/dx(5ex+2)=(5*d/dx(ex))+(0)

d/dx(5ex+2)=5*d/dx(ex)

-The derivative of ex is:

d/dx(eu)=eu*d/dx(u)

d/dx(ex)=ex*d/dx(x)

d/dx(5ex+2)=5*(ex*d/dx(x))

-The derivative of x is:

d/dx(xn)=nxn-1

d/dx(x)=1*x1-1

d/dx(x)=1*x0

d/dx(x)=1*(1)

d/dx(x)=1

d/dx(5ex+2)=5*(ex*1)

d/dx(5ex+2)=5*(ex)

d/dx(5ex+2)=5ex

5ex+2?

d/dx(cu)=c*du/dx where c is a constant.

d/dx(5ex+2)=5*d/dx(ex+2)

-The derivative of ex+2 is:

d/dx(eu)=eu*d/dx(u)

d/dx(ex+2)=ex+2*d/dx(x+2)

d/dx(5ex+2)=5*(ex+2*d/dx(x+2))

-The derivative of x+2 is:

d/dx(u+v)=du/dx+dv/dx

d/dx(x+2)=d/dx(x)+d/dx(2)

d/dx(5ex+2)=5*[ex+2*(d/dx(x)+d/dx(2))]

-The derivative of x is:

d/dx(xn)=nxn-1

d/dx(x)=1*x1-1

d/dx(x)=1*x0

d/dx(x)=1*(1)

d/dx(x)=1

-The derivative of 2 is 0 because it is a constant.

d/dx(5ex+2)=5*[ex+2*(1+0)]

d/dx(5ex+2)=5*[ex+2*(1)]

d/dx(5ex+2)=5*[ex+2]

d/dx(5ex+2)=5ex+2

Q: Derivative of 5ex plus 2

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2

2 - 8x

2

Derivative of x = 1, and since sqrt(x) = x^(1/2), derivative of x^(1/2) = (1/2)*(x^(-1/2))Add these two terms together and derivative = 1 + 1/(2*sqrt(x))

There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).

Related questions

2

Following the correct order of operations: derivative of x^2 + 6/2 = derivative of x^2 +3, which equals 2x

2 - 8x

Derivative of x = 1, and since sqrt(x) = x^(1/2), derivative of x^(1/2) = (1/2)*(x^(-1/2))Add these two terms together and derivative = 1 + 1/(2*sqrt(x))

2

The anti-derivative of X2 plus X is the same as the anti-derivative of X2 plus the anti-derivative of X. The anti derivative of X2 is X3/3 plus an integration constant C1 The anti derivative of X is X2/2 plus an integration constant C2 So the anti-derivative of X2+X is (X3/3)+(X2/2)+C1+C2 The constants can be combined and the fraction can combined by using a common denominator leaving (2X3/6)+(3X2/6)+C X2/6 can be factored out leaving (X2/6)(2X+3)+C Hope that helps

the hoover dam was the reason that the guy from toy story did his barbie 5ex

d/dx [sin(x) + 2] = cos(x)

There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).

The derivative of 2x2 + 4x + 8 is 4x+4.

lame

f(x) = 3x2 + 5x + 2fprime(x) = 6x + 5